DSC Study of Collagen in Disc Disease. (27th January 2010) - Skrzyński, S.; Sionkowska, A.; Marciniak, A.
Abstract : Differential scanning calorimetry (DSC) has been used to estimate the effect of disc disease on the collagen helix-coil transition and morphology for tissue extracted from patients during surgical operation. Forty discs were obtained from patients with degenerative disc disease undergoing surgery for low back pain. The patients were in the age between 20 and 70 years old. The specimens were kept wet during DSC experiment. The data allow the comparison between thermal stability of collagen tissue from healthy patients and from patients suffering from disc disease. In the paper the comparison between thermal helix-coil transition for collagen fibers from patients suffering from disc disease and collagen fibers from healthy organisms has been discussed. The heating rate has an influence on the position on denaturation temperatures of collagen in disc tissues. Higher helix-coil transition temperature of collagen in degenerated disc suggests that additional intermolecular cross linking of collagen fibers occurs. Denaturation temperatures of collagen in degenerated male disc possess smaller values than in female ones. Disc disease induces changes in collagen structure and leads to formation of additional crosslinks between collagen fibers.